Sociological Discourse-Analysis of the “Chinese Dream” Concept - N. B. Pomozova (Дискурс)
Introduction. Today, China and its foreign policy priorities largely determine global international politics. The PRC is one of the main partners of Russia. The need to understand the meanings that the Chinese leadership lays in its main political concepts determines the relevance of this study. The intensification of foreign policy demanded from the Chinese leadership an appropriate discourse, formalized in foreign policy concepts of a global scale. One of these concepts is the “Chinese Dream”. Its semantic content, at a first approximation, is opposed to the “American Dream”. If in the “American Dream” the interests of the individual and his/her well-being are at the forefront, then in the case of the “Chinese Dream” , on the contrary, at the top of the pyramid of values are the interests of the state, then society, and only then the individual.Methodology and sources. The methodological basis is sociological discourse analysis, combined with reflexive sociology, through which the author aims to expand the interpretation of the “Chinese dream” and reveal its additional, not obvious meanings. The empirical base was a sample of direct speeches by the leaders of China (Jiang Zemin, Hu Jintao, Xi Jinping) and their speeches at the CPC congresses. The works of Alvin Gouldner, Zygmunt Bauman, Michel Foucault were used as a theoretical basis. The author also analyzed some theoretical works of one of the main authors of the concept of the “Chinese dream” Li Junzhu, and in the context of the method of reflective sociology were studied and presented his biographical data.Results and discussion. From the standpoint of sociological discourse analysis and reflexive sociology, the article examines the context of the concept of the “Chinese dream” based on the publications of one of its authors Li Junzhu and the speeches of the PRC Presidents at the congresses of the Communist Party of China who used this formulation in their speeches. In the study, based on biographical facts, Li Junzhu shows socio -political reflection, as a result of which the concept under consideration was formulated. The academic background and experience of working with Chinese living abroad contributed to the theoretical development of the concept, which, as a first approximation, bears the load of an attractive national idea of the “American Dream” type.Conclusion. Discourse analysis also reveals a broader semantic content of the concept, which extends to China’s foreign policy and its vision of the system of international relations. When building a dialogue with China, it is useful to take into account this semantic construct, which is contained in the consedered concept.